2020
DOI: 10.1017/s1355617719000651
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Delivery of Memory Rehabilitation Following Stroke

Abstract: Objective:Rehabilitation of memory after stroke remains an unmet need. Telehealth delivery may overcome barriers to accessing rehabilitation services.Method:We conducted a non-randomized intervention trial to investigate feasibility and effectiveness of individual telehealth (internet videoconferencing) and face-to-face delivery methods for a six-week compensatory memory rehabilitation program. Supplementary analyses investigated non-inferiority to an existing group-based intervention, and the role of booster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 42 publications
2
42
0
Order By: Relevance
“…In this particular word-list we had four categories, namely Body Parts, Land Animals, Cleaning Supplies, and Water Animals. A more detailed description of the word-lists can be found in our previous studies (12)(13)(14)(15).…”
Section: Experimental Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In this particular word-list we had four categories, namely Body Parts, Land Animals, Cleaning Supplies, and Water Animals. A more detailed description of the word-lists can be found in our previous studies (12)(13)(14)(15).…”
Section: Experimental Study Designmentioning
confidence: 99%
“…Recent studies demonstrated that patients with vascular lesions can benefit from different cognitive interventions including face-name training to remember people's names and repetition-lag memory training, developed to increase recollection as opposed to familiarity in recognition memory tasks (9,10). There is also recent evidence of memory and attention improvement after computerized cognitive training and telehealth options for remote delivery of compensatory memory skills training after stroke (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Although, home therapy is valued for its effect to enhance the functional activity and participation level of stroke patients after discharge [44], results of our study indicate that there is still a time and/or travel problem for care professionals which makes it is still rather difficult, in current practice, to organize home therapy. To tackle time and travel difficulties, telemonitoring could be a feasible and effective alternative to improve recovery, and maintaining the benefits reached during inpatient rehabilitation [45][46][47]. Finally, we also observed that the attendance of the education module by the patients and informal caregivers was rather low.…”
Section: Discussionmentioning
confidence: 70%
“…Despite our intensive collaboration with the stroke care field in developing the program, the results of our process evaluation show that the program was only partly feasible. Implementation research shows that implementing complex interventions like ours is very challenging in an older population 48 .…”
Section: Discussionmentioning
confidence: 99%
“…It seems that complex interventions such as this in clinical practice for older stroke patients require a more intensive and stepwise implementation strategy such as described by Luker and Dowding 48,49 This method could be important to increase necessary knowledge of the key elements in the treatment protocol and enhance the collaboration between members of the rehabilitation teams.…”
Section: Discussionmentioning
confidence: 99%